Orientering om arbeidet med Norskrussisk juridisk ordbok - Senje, Aud Anna (Nordiske Studier i Leksikografi, 2012)
Norway and Russia cooperate in many fields, and bilateral contact at a professional level largely depends on translators and interpreters. There is thus a great need for specialized dictionaries. This particular dictionary is a result of my twelve years of work within the Norwegian police. It provides a basic vocabulary of terms used in the fields of legal and police work, but it is of course not comprehensive. Its profile is general, and the main emphasis is on criminal law. Not all entries are strictly ‘legal’. Terms that in a given context may have a specific meaning, but that are used so often in everyday language that they are perceived as ‘common’, are included. I have also included relevant terms from other special fields, such as finance, administration, medicine, environment, fisheries and IT. The dictionary is mainly intended for translators, interpreters, the police, the prosecuting authority, and government officials, e.g. at Norwegian diplomatic representations in Russia and the former Soviet republics. My purpose has been to create a practical tool, rather than a work of reference with detailed information about the differences between the Norwegian and the Russian legal systems. The supplement contains titles of selected Norwegian acts with suggested translations into Russian, and titles of selected conventions in Norwegian, Russian, and English.